2016
DOI: 10.4103/0970-9185.168263
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hemidiaphragmatic paresis after peripheral nerve stimulator versus ultrasound guided interscalene brachial plexus block

Abstract: Background and Aims:We compared interscalene brachial plexus block (ISBPB) using peripheral nerve stimulation (PNS) and ultrasound (US) techniques. The primary outcomes were the incidence of hemidiaphragmatic paresis (HDP) and the duration of the block. Secondary outcomes were the block success rate, time to conduct the block, onset of sensory block, and dermatomal spread, postoperative pain by Numeric Rating Scale (NRS), duration of postoperative analgesia and incidence of complications.Material and Methods:W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In our study, the incidence of hemidiaphragmatic paralysis, Horner's syndrome, and vascular injury was 20, 11, and 0%, respectively, though even lower incidences have also been claimed by some. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the incidence of hemidiaphragmatic paralysis, Horner's syndrome, and vascular injury was 20, 11, and 0%, respectively, though even lower incidences have also been claimed by some. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Supraclavicular blockade (SCB) under ultrasonic-guidance has recently increased its popularity [7] and is an alternative to anesthesia and analgesia in ASS [8]. SCB is performed in a more distal region that carries lesser anatomical risk for neurological damage and has lesser rates of hemidiaphragmatic paresis [9,10], Hoarseness or Horner's syndrome [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the positive effect of US guidance is not yet proven. Some studies have reported no minimization of complications using US guidance, despite the enhanced motor block achieved and the reduction in the time or number of needle passes required to perform an interscalene block …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported no minimization of complications using US guidance, despite the enhanced motor block achieved and the reduction in the time or number of needle passes required to perform an interscalene block. 9,10 A supraclavicular brachial plexus block (SCBB) is an alternative brachial plexus technique that is performed more distally than ISBB. SCBB has a reduced rate of hemidiaphragmatic paresis, 10 hoarseness, or Horner's syndrome, as well as fewer neurologic complications, when compared with ISBB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation